2008
DOI: 10.1055/s-2008-1027863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intracranial Aneurysms with 7 T versus 1.5 T Time-of-Flight MR Angiography – Initial Experience

Abstract: Our initial results indicate that image quality of intracranial aneurysms may benefit from the increased spatial resolution of 7 T TOF MRA compared with 1.5 T TOF MRA. Tailored scan protocols and optimized radiofrequency head coils are needed to further improve the image quality of 7 T TOF MRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 0 publications
0
34
0
4
Order By: Relevance
“…Gibbs et al [9] compared the delineation ability of 3T MRI with 1.5T MRI in patients known to have intracranial aneurysms [9] and found that 3T MR angiography had a greater ability to delineate intracranial aneurysms than 1.5T MRI. By contrast, Mönninghoff et al [10] reported that 7T MRI was superior in spatial resolution, but that all aneurysms were detected with 1.5T MRI, although the study was limited to only 10 patients with known intracranial aneurysms. Their findings suggest that high-tesla MRI should provide greater image quality and an accordingly more precise delineation of anatomical structure and a higher detection rate of intracranial aneurysms, as proven in our data.…”
Section: Discussionmentioning
confidence: 96%
“…Gibbs et al [9] compared the delineation ability of 3T MRI with 1.5T MRI in patients known to have intracranial aneurysms [9] and found that 3T MR angiography had a greater ability to delineate intracranial aneurysms than 1.5T MRI. By contrast, Mönninghoff et al [10] reported that 7T MRI was superior in spatial resolution, but that all aneurysms were detected with 1.5T MRI, although the study was limited to only 10 patients with known intracranial aneurysms. Their findings suggest that high-tesla MRI should provide greater image quality and an accordingly more precise delineation of anatomical structure and a higher detection rate of intracranial aneurysms, as proven in our data.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, local RF transmit coils excite a rather small RF volume where entering RF pulses are not pre-saturated, which potentially contributes to the hyperintense signal [34]. This interesting feature of T1-weighted MRI at 7 Tesla led to a shift of the focus of ultra-high-field brain imaging from structural to vessel diagnostics [10,13,31,35,36]. One of the first studies to assess the feasibility and diagnostic value of intracranial MRA at 7 Tesla was introduced by Maderwald et al [31].…”
mentioning
confidence: 99%
“…Mön-ninghoff et al compared the diagnostic ability of 7 T versus 1.5 T time-of-flight (TOF) MRA in patients with intracranial aneurysms. They could prove a diagnostic benefit due to the increased spatial resolution of 7 T TOF MRA [10,13]. After successful demonstration of the feasibility of 7 Tesla brain imaging, first field strength comparison trials were conducted ( • " Fig.…”
mentioning
confidence: 99%
“…However, TOF MRA at high field strength suffers from increased artifacts. Initial results have shown advantages of ultra-high field in structural analysis of aneurysms or arterio-venous malformations [53][54][55] (Fig. 3b).…”
Section: Vesselsmentioning
confidence: 99%